Single-walled carbon Nanotube-Encapsulated polyoxometalates for Wide-Range humidity PEM fuel cells - Chenyu Liu; Qinghao Lin; Jujia Zhang; Qin Liu; Xianglong Wan; Wentuan Bi (Fuel, 2026)

Atmospheric Deposition of Multi-Class Substances into the Ocean: Synthesis of Fluxes, Seasonal Spatial Patterns and Ecological Risks - Qinghao Lin; Xianliang Yi; Junyi Wang; Yiwen Zhang; Jingjing Zhan (Journal of Marine Science and Engineering, 2026)
Atmospheric deposition is increasingly recognized as a significant pathway transporting diverse substances from land to the ocean. However, significant uncertainties persist regarding the magnitude, spatial variability, and ecological implications of these inputs into the ocean. This study compiles and standardizes observational datasets from published sources to provide a cross-substance synthesis of atmospheric concentrations, deposition fluxes, seasonal patterns, and ecological risks. The analysis covers major substance categories, including nutrients, trace metals, microplastics, POPs and other emerging pollutants. The novelty of this work lies in its cross-pollutant approach and the integration of seasonal dynamics, particularly for winter deposition. Global results show widespread deposition across the world’s oceans, with consistently elevated concentrations in densely populated coastal regions and detectable levels even in remote areas, underscoring the role of long-range transport. Our analysis reveals pronounced winter peaks in regions like the Bohai Sea and the Baltic Sea, highlighting a critical but often overlooked seasonal window. Strong nearshore-to-offshore gradients across most substances indicate dominant influences from coastal anthropogenic emissions. Ecological risk assessment using the Risk Quotient method suggests that risks are generally low but spatially heterogeneous, with hotspots in regions of intensive human activity. Overall, this synthesis highlights the importance of atmospheric pathways in shaping marine substance distributions and emphasizes the need for improved monitoring and modeling to better quantify episodic deposition processes under future environmental change.

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Photo-responsive polyprodrug supramolecular assemblies with self-accelerated subcellular delivery for synergistic photochemotherapy - Ming Liu; Zhenduo Zhao; Ming Li; Yitian Chen; Yicheng Wang; Xuehua Lin; Xinyu Wang; Qinghao Zhou; Zhishen Ge; Yongan Tang; Yibin Deng; Yuliang Zhao; et al. (Science Bulletin, 2026)

A coupled fluorescence assay for high-throughput screening of polyurethane-degrading enzymes - Liujun YANG; Xianjun DENG; Renju LIU; Jianyang LI; Junyao ZHAI; Xiaoxiao MA; Shiyang YOU; Qinghao HE; Arthur K.L. LIN; Zongze SHAO; Hongyuan LU (Journal of Hazardous Materials, 2026)

CuS@Pt@ZIF-8 mediated Fenton-like nanozyme for synergistic photothermal and chemodynamic antibacterial wound healing therapy - Qinghao He; Mingxin He; Hao Zhang; Pan Xu; Xiantao Lin; Jianbo Zhang; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Drilling Response Law for PDC Bit Cutting and Breaking Rock: Governing Equation and Experiment Validation - Huihui Xie; Peng Lin; Zhenhao Xu; Jintao Kang; Qinghao Zhang (Rock Mechanics and Rock Engineering, 2025)

A temperature compensated fiber probe for highly sensitive detection in virus gene biosensing - Xiaopeng Han; Yu Zhang; Yundong Zhang; Qinghao Song; Wuliji Hasi; Siyu Lin; Fan Wang (Analytica Chimica Acta, 2024)

A single-electrode evaluation method used for analyzing the working mechanism and capability of integrated membrane capacitive deionization - Qinghao Wu; Qifeng Wang; Chen Yu; Shanfu Lu; Kun Lin; Yan Xiang; Kuichang Zuo; Doron Aurbach; Dawei Liang (Desalination, 2024)

Nonparametric estimation for planetary soil based on numerical simulation of penetration process - Han Huang; Xintao Yang; Shucai Xu; Lin Yang; Haozhe Wang; Zhixin Xiang; Qinghao Yan (Advances in Space Research, 2023)

The Chinese species of skipper butterflies in the tribe Tagiadini Mabille, 1878 (Lepidoptera: Hesperiidae): insights from phylogeny, hostplants, and biogeography - Li Shen; Jianqing Zhu; Yuxiang Lin; Jie Fang; Yongqiang Wang; Liying Tang; Qinghao Zhao; Mengqi Xiao; Feiyu Duan; Qunxiu Liu; Weidong Yu; Weibin Jiang (Organisms Diversity & Evolution, 2022)

3-Dimensional Modeling and Attitude Control of Multi-Joint Autonomous Underwater Vehicles - Lin Yu; Qinghao Meng; Hongwei Zhang (Journal of Marine Science and Engineering, 2021)
To achieve rapid and flexible vertical profile exploration of deep-sea hybrid structures, a multi-joint autonomous underwater vehicle (MJ-AUV) with orthogonal joints was designed. This paper focuses on the 3-dimensional (3D) modeling and attitude control of the designed vehicle. Considering the situation of gravity and buoyancy imbalance, a 3D model of the MJ-AUV was established according to Newton’s second law and torque balance principle. And then the numerical simulation was carried out to verify the credibility of the model. To solve the problems that the pitch and yaw attitude of the MJ-AUV are coupled and the disturbance is unknown, a linear quadratic regulator (LQR) decoupling control method based on a linear extended state observer (LESO) was proposed. The system was decoupled into pitch and yaw subsystems, treated the internal forces and external disturbances of each subsystem as total disturbances, and estimated the total disturbances with LESO. The control law was divided into two parts. The first part was the total disturbance compensator, while the second part was the linear state feedback controller. The simulation results show that the overshoot of the controlled system in the dynamic process is nearly 0 rad, reaching the design value very smoothly. Moreover, when the controlled system is in a stable state, the control precision is within 0.005%.